Efficient algorithms for block downdating of least squares solutions - Yanev, Petko I.; Kontoghiorghes, Erricos John (My University, 2004)
Five computationally efficient algorithms for block downdating of the least squares solutions are proposed. The algorithms are block versions of Givens rotations strategies and are rich in BLAS-3 operations. They efficiently exploit the triangular structure of the matrices. The theoretical complexities of the algorithms are derived and analyzed. The performance of the implementations confirms the theoretical results. The new strategies are found to outperform existing downdating methods.
Keywords: Least squares; Algorithms; Computational complexity